A partial element equivalent circuit‐metamodel combination for fast tolerance analysis of electromagnetic systems. Issue 10 (24th June 2021) - Ferranti, Francesco; Antonini, Giulio; Nakhla, Michel
Abstract: In this letter, we propose a combination of the partial element equivalent circuit method with metamodelling in order to achieve fast tolerance analysis of electromagnetic systems. The proposed model combination can be interpreted as a multifidelity modeling approach. This technique is inspired by the multilevel Monte Carlo method and provides great benefits in terms of computational resources.